Management of Progressive Fibrosing Interstitial Lung Diseases (PF-ILD) - Copeland, Carla R.; Lancaster, Lisa H. (Frontiers in Medicine, 2021)
Progressive fibrosing interstitial lung diseases (PF-ILD) consist of a diverse group of interstitial lung diseases (ILD) characterized by a similar clinical phenotype of accelerated respiratory failure, frequent disease exacerbation and earlier mortality. Regardless of underlying disease process, PF-ILD progresses through similar mechanisms of self-sustained dysregulated cell repair, fibroblast proliferation and alveolar dysfunction that can be therapeutically targeted. Antifibrotic therapy with nintedanib or pirfenidone slow lung function decline and are the backbone of treatment for IPF with an expanded indication of PF-ILD for nintedanib. Immunosuppression is utilized for some subtypes of PF-ILD, including connective tissue disease ILD and hypersensitivity pneumonitis . Inhaled treprostinil is a novel therapy that improves exercise tolerance in individuals with PF-ILD and concomitant World Health Organization (WHO) group 3 pulmonary hypertension. Lung transplantation is the only curative therapy and can be considered in an appropriate and interested patient. Supportive care, oxygen therapy when appropriate, and treatment of comorbid conditions are important aspects of PF-ILD management. This review summarizes the current data and recommendations for management of PF-ILD.